Epidemiology and decision-making in theileriosis control - Perry, Brian D.; Lessard, P.; Mukhebi, A.W.; Norval, R.A.I. (International Laboratory for Research on Animal Diseases, 1989)
Examines circumstances under which three basic theileriosis control methods might be used and proposes a conceptual framework with which a decision might be made on the best method to use in a given area.